Breast self examination and mammogram HBM questionnaire - Moey, Soo Foon; Ramli, Hanis Aisyah; Abdul Mutalib, Aainah Mardhiah (2019)
Breast cancer is the commonest cancer that inflicts women in most part of the world accounting for 18% of all cases in 2012 and the fourth most common cause of cancer related deaths (Youlden et al., 2014). Data from the National Cancer Registry (NCR) of Malaysia for 2004 reported age standardised incidence rate (ASR) of 46.2 per 100,000 women which translates to the development of breast cancer of 1 in 20 women in the country while data from the World Health Organization (WHO), 2012 reported ASR of 38.7 and mortality ASR of 18.9 per 100,000 of the population. In the past decade there have been indications of sustainable reduction of mortality in the western countries which is linked to significant breast cancer control due mainly to increased breast awareness and early detectability of the disease as well applying appropriate therapy to women inflicted with the disease (Yip et al., 2006). The favourable breast cancer survival rate in the western countries (89% in five years in cases registered with US SHEER program in 1995-2000) is as a result of the prevalence of the screening programs (Parkin et al., 2005). When mammographic screening started in the developed countries, breast self-examination (BSE) was not encouraged. However, in developing countries that lack mammographic screening resources, BSE has been recommended and still continues to be promoted as an appropriate method in detecting breast cancer as previous studies have indicated its’ effectiveness in which 25% of breast cancer were detected by BSE and 56% by CBE or after patient noted abnormalities and were evaluated (Roth et al., 2012; Allen et al., 2017). In Malaysia, breast cancer awareness is relatively poor amongst Malaysian women indicated by poor uptake of regular mammography screening (Yip, Pathy & Teo, 2014). In general, Malaysian women present with late stages of breast cancer compared to their counterparts from developing countries. Early detection of the disease could be promoted by mammography, clinical breast examination (CBE) and SBE. Mammographic screening in Malaysia is generally opportunistic in nature and targets women attending women’s wellness clinics and maternal and child clinics run by the Ministry of Health. Mammographic screening remains under-utilized and is dependant in part of the women’s initiative to self-refer for screening. The breast cancer five -years survival rate from 1993-1997 reported by the breast cancer registry, University Malaya Medical Centre (UMMC) is 57% (Yip, Pathy & Teo, 2014). Newer records to study the five-years survival trend from the same centre could not be obtained. However, a 43.5% five-years survival rate from a total of 868 women diagnosed between January 2005 and December 2009 from secondary data obtained from the Breast Cancer Registry and medical records of breast cancer patients admitted to Hospital Kuala Lumpur (Ibrahim et al., 2012) indicated a down trend of survival from breast cancer. It is also reported that the overall breast cancer mortality rates have increased in several countries with the largest rises recorded in Malaysia of 7% per year from 1997 to 2008 with the rate of increase higher for females above 50 years of age (Youlden et al., 2014). The survival rate of 81.7% in stage 1 could possibly be improved to 90% or more with improved treatment (Yip, Pathy & Teo, 2014) which indicated early diagnosis to better survival. If survival is dependant mainly on early diagnosis and treatment, it is therefore indicative that this is the area that we need to address to detect the disease early or risk reduction. The main determinants of survival are early detection which in part is dependent on disease awareness and uptake of screening. The three main methods of early detection are BSE, CBE and mammography. While BSE and CBE can aid in down staging of symptomatic disease, mammography allows detection of breast cancer in the early stage where cure is possible Mammographic screening in Malaysia is generally opportunistic in nature and targets women attending women’s wellness clinics and maternal and child clinics run by the Ministry of Health. Mammographic screening remains under-utilized and is dependant in part of the women’s initiative to self-refer for screening. One of the fundamental factors that affect mortality is the stage of presentation of the disease for medical care (Taymoori et al., 2006; Teh et al., 2015; Yip & Pathy, 2014, Yip e t al., 2006,). In Malaysia, late presentation of breast cancer is common which would be attributed to geographical isolation and poverty with further probable barriers such as psychosocial and cultural beliefs (Teh et al., 2015). Unfortunately stage of diagnosis of breast cancer is not available from NCR data. Presently, stage at diagnosis can only be obtained from hospital epidemiology data which may different between hospitals. Data from UMMC for a 12 years period from 1993 to 2004 indicated that about 60-70% of women presented with early stage (stages 1-2) while 30-40% presented with late breast cancer (stages 3-4). This compares unfavourably with the western countries that reported more than 80% of the women present with early stage lesions (Yip et al., 2006). However, the Penang Cancer Registry for 1994-1998 reported stage 1 breast cancer comprised 5.8% at diagnosis while stage 2 accounted for 46.9%, stage 3 at 22.2% and stage 4 at 15.5% (Zarihah et al., 2003). Further Yip, Pathy and Teo (2014) also reaffirmed that Malaysian women present with late stages of the disease compared to western countries and Singapore. Theoretically based factors are important to be employed when studying breast cancer screening behaviours to maximize the interventional impact (Taymoori et al., 2012). The health belief model is one of the models that can be used to explain factors influencing BSE and mammography screening behaviours in order to plan and implement breast screening programs in various populations (Allahverdipour et al., 2011; Shirazi et al., 2006; Noroozi et al., 2011; Taymoori et al., 2009). The HBM is derived from the theory that a person behavioural change is based primarily on five factors namely perceived susceptibility (women’s opinion of the chances of getting breast cancer), perceived severity (person’s opinion of the seriousness of the condition), perceived benefits (opinion of the effectiveness of some advised action to reduce risk such as BSE and mammography) and perceived barriers to having BSE and mammography.